PENGARUH LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS (Studi Kasus Pada Perusahaan Sub Sektor Tekstil Dan Garmen Di BEI Tahun 20172019) - Reza Audia W.A; Budi Wahono; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT  The purpose of this study was to determine the effect of Liquidity, Leverage, and Profitability on Financial Distress (Case Study of Textile and Garment Sub Sector Companies on the Stock Exchange in 2017-2019). The population in this study uses the textile and garment sub-sector companies on the Stock Exchange in 2017-2019 with a total of 22 companies. Determination of the sample is based on the purposive sampling method, using sample determination criteria, namely the textile and garment sub-sector companies listed on the Stock Exchange in 2017-2019, the textile and garment sub-sector companies that publish financial statements in 2017-2019, companies that have full information on data related to this research. Based on the sample criteria. Based on the sample criteria, 20 companies were used as samples. Data analysis techniques in this study used logistic regression analysis. The results showed that liquidity and leverage did not have a significant effect on financial distress, whereas profitability had a significant negativeeffect onfinancial distress.   Keywords: Liquidity, Leverage, Profitability and Financial Distress.